Pengaruh Mata Kuliah Kewirausahaan dan Penggunaan Media Sosial terhadap Minat Berwirausaha: Studi pada Mahasiswa Program Studi Pendidikan Bisnis Stambuk 2022 Fakultas Ekonomi Universitas Negeri Medan - Junedi Sugianto Pakpahan; Ivo Selvia Agusti (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Entrepreneurial interest among university students has become an important concern in supporting the development of young entrepreneurs capable of creating employment opportunities. Entrepreneurship education and the rapid growth of social media, particularly TikTok, are considered strategic factors in strengthening students' entrepreneurial intentions. This research employed a quantitative ex-post facto approach involving 63 Business Education students of the 2022 cohort at the Faculty of Economics, Universitas Negeri Medan, selected through total sampling. Data were collected using questionnaires and academic documentation, then analyzed through multiple linear regression, t-test, F-test, coefficient of determination, and classical assumption tests using SPSS version 25. The findings indicate that entrepreneurship courses have a positive and significant influence on entrepreneurial interest. TikTok social media usage also demonstrates a positive and significant contribution to students' entrepreneurial interest. Simultaneously, both variables significantly explain entrepreneurial interest with an Adjusted R Square value of 0.474, indicating that 47.4% of the variation in entrepreneurial interest is explained by the proposed model, while the remainder is influenced by other factors. These findings reinforce the importance of integrating entrepreneurship learning with productive digital media utilization to foster entrepreneurial mindsets among university students. The study contributes empirical evidence regarding the complementary role of entrepreneurship education and digital platforms in supporting entrepreneurship development within higher education.